Expression orale d'un public d'adultes de niveaux B1, B2 et C1 à l'Alliance Française de Johannesburg : blocages et remédiations par le biais de l'élaboration et de la mise en oeuvre de fiches pédagogiques - Léger-Broschart, Isabelle (French Language and Literature, 2017)
This research and development dissertation researches the oral expression of adults of levels B1, B2 and C1 attending conversation classes at the French Alliance of Johannesburg; it aims to identify obstacles in oral expression and to propose remediation tools. The students were questioned on their expectations, needs and difficulties, and teachers on their needs and course techniques, through questionnaires. Pedagogical worksheets were developed for the teachers, and were implemented in the researcher's own conversation classes, after which learners' satisfaction was evaluated. The pedagogical worksheets presented in this study attempt as far as possible to meet the expectations, needs and difficulties expressed by the learners, and to provide practical assistance to the teachers of conversation classes.